Pengaruh Price Perception, Product Variety, dan Service Quality terhadap Repurchase Intention di Inspirasi Coffee Kediri - Saffa Alisha Jasmine; Diana Ambarwati; Nuril Aula Munawaroh (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to examine the effect of Price Perception, Product Variety, and Service Quality on Repurchase Intention among consumers of Inspirasi Coffee in Kediri City. This research employs a quantitative approach using a survey method by distributing questionnaires to 96 respondents who have previously made purchases at Inspirasi Coffee. The data analysis technique applied is multiple linear regression using SPSS software. The results indicate that partially, Price Perception, Product Variety, and Service Quality have a positive and significant effect on Repurchase Intention. Simultaneously, these three independent variables also have a significant influence on consumers’ repurchase intention. Therefore, the management of Inspirasi Coffee is advised to pay attention to price affordability, product variety innovation, and service quality improvement in order to enhance customers’ repurchase intention.